Plasmonic signal modulation at sub-GHz frequency via on-chip integration of tunnel junctions - Wang Fangwei; Huang Baohu; Liu Yan; Gao Siping; Guo Yongxin; Zhang Qian (Nanophotonics)
Plasmonic technology offers one of the most promising solutions to achieve on-chip integration of nanoscale and fast modulation circuits using surface plasmon polaritons (SPPs) as the information carriers. However, the potential of modulation speed of plasmonic signals has not been fully tapped. In this paper, we have demonstrated the plasmonic signal can be modulated at the bandwidth of sub-GHz (>100 MHz) via the on-chip integration of tunnel junctions. We also find that the lifetime of tunnel junctions under AC conditions can be improved significantly compared with the DC counterparts, which allows us to investigate and visualize the real-time breakdown process of tunnel junctions. Our implementation of plasmonic signal modulation at sub-GHz frequency paves the way toward potential industrial applications of on-chip plasmonic circuits.